Reposting the ‘17+8 People's Demands’: Social practice among students in the digital field - Fakhris Aulady; Agus Machfud Fauzi (SIMULACRA: JURNAL SOSIOLOGI, 2026)
The reposting of content related to social movements has emerged as a prevalent practice among students, particularly following the widespread circulation of the “17+8 People’s Demands” poster. Existing scholarship has largely interpreted this phenomenon as a mere spectre of participation, predominantly situated within communication and political science perspectives, thereby overlooking its significance as a form of social practice. This study seeks to address this gap by employing Pierre Bourdieu’s framework of social practice, combined with a qualitative methodology encompassing semi-structured interviews and systematic coding procedures adapted from Robert C. Bogdan and Sari Knopp Biklen. Such an approach facilitates an in- depth exploration of participants’ subjective meanings, strategic actions, and reflexive considerations. Furthermore, this study examines variations in social practices across friendship networks, campus culture, and the symbolic power embedded within online environments. Reposting behavior reflects socially embedded, habitus-driven practices involving reflexivity, solidarity, risk negotiation, and symbolic capital considerations within digital communities. Accordingly, this research offers an original contribution by conceptualizing digital activism as a form of social practice dynamically constituted through habitus, capital, and digital environments. In doing so, it extends Bourdieu’s theoretical framework into the domain of social media and underscores that social practices are equally enacted within digital contexts.